(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2026)
This article analyzes the artistic and aesthetic features of the works of Erkin Vohidov, one of the prominent representatives of modern Uzbek literature. Selected poems of the poet that embody universal human values are analyzed, and the spiritual and moral ideas advanced therein, their artistic interpretation, as well as the poetic expressive means employed, are comprehensively examined. Special attention is given to the depiction of universal human qualities such as the awareness of national identity, devotion to folk values, sincerity, friendship, and humanity, all of which are explored through a scholarly approach.